Cultivating harmony across borders: Chinese cultural values and corporate communication in global contexts - Xia, Shizhou; Liu, Wenyu (Frontiers in Communication, 2025)
IntroductionAmid China’s rising global economic presence, the role of cultural dynamics in corporate communication is increasingly crucial, particularly in cross-cultural contexts. This study examines how Chinese cultural values are embedded within corporate communication practices of Chinese enterprises operating internationally, specifically within African markets.MethodsThis study employed a qualitative, cross-sectional research design, analyzing corporate communications at a single point in time to capture a contemporary snapshot of discursive practices. The study utilized content analysis and discourse analysis of textual data collected from the official English-language websites of 200 Chinese corporations operating across diverse sectors in Africa. This primary dataset was complemented by illustrative corporate social responsibility (CSR) cases drawn from the Sino-Africa Cooperation: Corporate Social Responsibility Guide (2021) to provide in-depth, practical examples.ResultsThe analysis identified three prominent and interwoven cultural values guiding the corporate communications of Chinese corporations: embracing harmony through collectivism, pursuing excellence through continuous improvement, and practicing integrity with responsibility. These values are consistently articulated in corporate philosophy statements and CSR narratives and are exemplified through case studies of major firms such as Huawei, China Communications Construction Company, and the TEDA Suez Eco-Industrial Park, which emphasize mutual benefit, sustainability, and deep community integration.DiscussionThe findings demonstrate that these culturally informed communication practices both reflect China’s broader socio-economic initiatives, such as the Belt and Road Initiative, and actively reproduce alternative, non-Western development paradigms. The study further illuminates the strategic navigation by Chinese firms between presenting their core values as universal business principles and framing them as unique expressions of Chinese cultural identity to build legitimacy with diverse international stakeholders.ContributionThis research provides an empirically grounded, non-Western perspective on how cultural values are strategically deployed in corporate discourse. It also offers timely, practical insights for international business leaders, policymakers, and other stakeholders on engaging with Chinese companies, underscoring the central role that cultural values play in shaping contemporary global business interactions.